An X-ray view of central engines of low-luminosity quasars (LLQSO) in the local Universe. Issue 2 (19th July 2018) - Laha, Sibasish; Ghosh, Ritesh; Guainazzi, Matteo; Markowitz, Alex G
ABSTRACT: We have carried out a systematic X-ray spectral analysis of a sample of low-luminosity quasars (LLQSO) to investigate the nature of the central engines of these sources. The optically selected LLQSO sample consists of close, known bright active galactic nuclei (AGN) which serves as an important link between the powerful quasars at higher redshift and local Seyfert galaxies. We find that although the bolometric luminosities of the LLQSOs are lower than those of the higher redshift quasars by almost an order of magnitude, their distribution of the Eddington rate λ _ Edd is similar. We detect a strong anticorrelation between αOX and L_2500 A, as has also been detected in several other quasar studies with large sample sizes, indicating that as the UV luminosity of the source increases, the X-ray luminosity decreases. We do not detect any significant neutral obscuration (N_H10^22cm^-2 ) in the X-ray spectra of the LLQSOs, and hence rule out obscuration as a possible cause for their lower luminosity. We conclude that the central engines of the LLQSOs function similarly to those of the higher redshift quasars, and the difference is possibly because of the fact that the LLQSOs have lower black hole masses. We do not find any correlation between the molecular gas in the host galaxies and accretion states of the AGN. This indicates that the presence of molecular gas in the host galaxies of the LLQSOs does not significantly influence the instantaneous accretion rates of their SMBHs.